The context for the March 2024 Budget - Carl Emmerson; Martin Mikloš; Isabel Stockton (Institute for Fiscal Studies (IFS), 2024)
Chancellor Jeremy Hunt will announce his second Budget, and fourth fiscal event, on Wednesday 6 March. This will possibly be the final fiscal event of the current parliament. With the big rise in tax revenues as a share of national income since 2019 only being partially offset by the cuts to National Insurance contributions that came into effect this January, Mr Hunt may be looking for opportunities to announce and implement further tax cuts. This report sets out how the fiscal outlook has changed since November. A key change is that the outlook for spending on debt interest has improved slightly. Despite this, the fact remains that public sector net debt will barely be on course to fall in five years' time, and only on the basis of plans for fuel duties, business rates and, in particular, day-to-day spending on public services that are unlikely to be realised. There is therefore only a weak economic case for another sizeable net tax cut in the forthcoming Budget.
Keywords: 330; Government finances and spending; Election 2024; Spring Budget 2024; Government spending; Public finance